An Analysis of the Fulfillment of Female Workers' Health Through the Healthy and Productive Women Workers Movement (GP2SP) - Nur Rofik Ajiria; Sunarto Kadir; Sri Manovita Pateda (Indonesian Journal of Global Health Research, 2025)
Female workers face various risks that can potentially disrupt their health in the workplace, thus requiring proper health maintenance and protection. This study aims to analyze the fulfillment of female workers' health needs through the implementation of the Healthy and Productive Female Workers Movement (GP2SP) program in Asparaga sub-district, Gorontalo Regency. This research utilized a descriptive qualitative design. The study's sample consisted of 26 informants, including 3 key informants (the Head of the Occupational Health Program, the Head of the Asparaga Community Health Center, and the GP2SP Program Coordinator) and 23 female workers selected using probability sampling. The instruments used were observation sheets and interview questions. Data were analyzed using the Miles and Huberman model. The results show that the GP2SP program successfully met the health needs of the female workers. This is evidenced by various activities, including: Routine health check-ups, Health education in the work environment, Regular body weight and Body Mass Index measurements, Provision of adequate nutritional intake, Monthly health check-ups for pregnant women, Availability of lactation corners and breast milk storage facilities. Overall, this study concludes that the GP2SP program successfully fulfilled the health, nutrition, and maternal and breastfeeding health aspects for female workers in the Asparaga sub-district.